Virtual reality and assessment of neurocognitive functions - Đurić Jočić, Dragana; Pavlović, Viktor; Kolundžija, Đurđevka (Engrami, 2024)
Virtual reality and assessment of neurocognitive functionsThe expansion of technology over the past twenty years has led to the digitalization of psychological assessment tools and the development of new evaluation techniques, with virtual reality (VR) standing out in terms of clinical utility. VR involves temporarily suspending contact with reality and placing a person in a simulated, experimentally controlled situation that resembles a real environment. Immersion in digital reality can be either complete or partial, a dimension that depends on the technological characteristics of the virtual system and affects psychological processes and the participant's experience during the assessment process. Instead of traditional paper-and-pencil tests, the virtual environment represents a completely new medium and experimental situation that we have not previously encountered, generating a wealth of ideas in psychology. Research often investigates the ecological validity or convergent validity between psychological tests and situations created in VR, particularly with groups of individuals with dementia and schizophrenia. Executive functions are typically the focus of measurement, and there is particular interest in the potential of VR-based assessment to enable early detection of cognitive impairments in healthy individuals. The paper discusses the advantages of VR over traditional neuropsychological tests, as well as its drawbacks, particularly the phenomenon of virtual reality sickness, which limits the duration of testing and reduces the validity of measurements. It is already evident that VR techniques will be implemented into psychological test batteries to increase the sensitivity and ecological validity of neuropsychological assessments, and recommendations will be provided on how VR can be clinically utilized in the rehabilitation and therapy of cognitive functions.Key words: virtual reality, neurocognitive functions, neuropsychological assessment